2007
DOI: 10.1002/jnr.21561
|View full text |Cite
|
Sign up to set email alerts
|

Cx29 and Cx32, two connexins expressed by myelinating glia, do not interact and are functionally distinct

Abstract: In rodents, oligodendrocytes and myelinating Schwann cells express connexin32 (Cx32) and Cx29, which have different localizations in the two cell types. We show here that, in contrast to Cx32, Cx29 does not form gap junction plaques or functional gap junctions in transfected cells. Furthermore, when expressed together, Cx29 and Cx32 are not colocalized and do not coimmunoprecipitate. To determine the structural basis of their divergent behavior, we generated a series of chimeric Cx32-Cx29 proteins by exchangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 57 publications
5
54
0
Order By: Relevance
“…Rather, Cx32 and Cx47 are the primary connexins on the oligodendrocyte side of A:O GJs. Like Cx29 (Ahn et al 2007), Cx31.3 does not form GJ plaques or functional GJs by either dye transfer or electrophysiological assays in transfected cells. How Cx29/Cx31.3 functions in oligodendrocytes is unknown, but its localization on the adaxonal membrane of small myelinated axons (facing the periaxonal space) leads to the speculation that it forms hemichannels (Altevogt et al 2002;Kamasawa et al 2005;Kleopa et al 2004;Menichella et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Rather, Cx32 and Cx47 are the primary connexins on the oligodendrocyte side of A:O GJs. Like Cx29 (Ahn et al 2007), Cx31.3 does not form GJ plaques or functional GJs by either dye transfer or electrophysiological assays in transfected cells. How Cx29/Cx31.3 functions in oligodendrocytes is unknown, but its localization on the adaxonal membrane of small myelinated axons (facing the periaxonal space) leads to the speculation that it forms hemichannels (Altevogt et al 2002;Kamasawa et al 2005;Kleopa et al 2004;Menichella et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Gap junction channels are formed among astrocytes (A/A), among oligodendrocytes (O/ O), and between oligodendrocytes and astrocytes (O/A), which results in formation of panglial networks (Wallraff et al, 2006;Maglione et al, 2010;Wasseff and Scherer, 2011). Since Cx29 does not form functional gap junction channels in cell culture experiments and Cx26 expression is limited to few gray matter astrocytes, panglial networks are mainly formed by astrocytic Cx43 and Cx30 and oligodendrocytic Cx47 and Cx32 (Ahn et al, 2008;Giaume and Theis, 2010;Nagy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The observed variation of most of the analyzed samples is between 0.80 and 1.20 regarding to the calibrator sample. All RQ results of this analysis are listed in Supplementary Table I. display any abnormalities [Eiberger et al, 2006], and it was shown that the protein does not form fully functional intercellular channels [Ahn et al, 2008]. Another gap junction protein seems to be important for oligodendrocytic homeostasis although not expressed by oligodendrocytes: GJA1 is expressed by astrocytes, but was shown to be the interacting hemichannel partner of GJA12 [Orthmann-Murphy et al, 2007b].…”
Section: ])mentioning
confidence: 97%